Midwife-led birthing centres in four countries: a case study - Oliva Bazirete; Kirsty Hughes; Sofia Castro Lopes; Sabera Turkmani; Abu Sayeed Abdullah; Tasleem Ayaz; Sheila E. Clow; Joshua Epuitai; Abdul Halim; Zainab Khawaja; Scovia Nalugo Mbalinda; Karin Minnie; et al. (BMC, 2023)
Abstract Background Midwives are essential providers of primary health care and can play a major role in the provision of health care that can save lives and improve sexual, reproductive, maternal, newborn and adolescent health outcomes. One way for midwives to deliver care is through midwife-led birth centres (MLBCs). Most of the evidence on MLBCs is from high-income countries but the opportunity for impact of MLBCs in low- and middle-income countries (LMICs) could be significant as this is where most maternal and newborn deaths occur. The aim of this study is to explore MLBCs in four low-to-middle income countries, specifically to understand what is needed for a successful MLBC. Methods A descriptive case study design was employed in 4 sites in each of four countries: Bangladesh, Pakistan, South Africa and Uganda. We used an Appreciative Inquiry approach, informed by a network of care framework. Key informant interviews were conducted with 77 MLBC clients and 33 health service leaders and senior policymakers. Fifteen focus group discussions were used to collect data from 100 midwives and other MLBC staff. Results Key enablers to a successful MLBC were: (i) having an effective financing model (ii) providing quality midwifery care that is recognised by the community (iii) having interdisciplinary and interfacility collaboration, coordination and functional referral systems, and (iv) ensuring supportive and enabling leadership and governance at all levels. Conclusion The findings of this study have significant implications for improving maternal and neonatal health outcomes, strengthening healthcare systems, and promoting the role of midwives in LMICs. Understanding factors for success can contribute to inform policies and decision making as well as design tailored maternal and newborn health programmes that can more effectively support midwives and respond to population needs. At an international level, it can contribute to shape guidelines and strengthen the midwifery profession in different settings.